Multi-objective optimization study on heat transfer performance of solar salt in non-circular twisted tube heat exchanger based on entropy generation number and NSGA II - Han, Yong; Wu, Yong-Gang; Meng, Fan-Lin; Zhang, Can-Can; Wu, Yu-Ting; Wu, Xue-Hong; Jin, Ting-Xiang (International journal of thermal sciences, 2025)
The optimization between heat transfer enhancement and flow resistance reduction of solar salt in a noncircular twisted tube heat exchanger (NCTTHX) was studied. Firstly, the effects of axis ratio (β), inlet velocity (uin,solarsalt) and pitch (Pt) on heat transfer and flow resistance of the solar salt were numerically investigated. Secondly, the mathematical model of the entropy balance for heat transfer process of the solar salt was established, where the modified heat transfer entropy generation number (HTEGN, χ) is proposed. Moreover, the modified ZS-RSM methodology was utilized for the regression of Nusselt number (Nuoval), heat transfer effectiveness (ε) and the HTEGN (χ). Finally, the integration of the NSGA-II algorithm and modified ZS-RSM methodology was utilized for the optimization of heat transfer enhancement and flow resistance reduction for solar salt in the NCTTHX. The results show that: the torsion force is the main reason that can improve the heat transfer performance, where ether the increase of β and uin,solarsalt or the decrease of Pt can strengthen the effect of the torsion force. There is a coincidence opposite variation trend between χ and ε at constant Re. χ can effectively describe the effect of changes in inlet temperature ratio tao on heat transfer performance, whereas ε cannot. The prediction by the modified ZS-RSM methodology is well aligned with the numerical results. When the minimum χ is added as the objective function, the flow resistance and heat transfer entropy generation number decreases by 6 % and 0.6 %, respectively; however, the energy efficiency ratio increases by 6.2 %. •Heat transfer mechanism of the solar salt in the NCTTHX is investigated.•The heat transfer entropy generation number χ is proposed.•The modified ZS-RSM regression model is established.•The NSGA-II is utilized for the optimization of the NCTTHX.